An Anatomical Study of the Sural Nerve: A Review of Cadaveric Data and Comparison with 3 Tesla MRI. Issue 1 (January 2022) - Ghetti, Claudio B.; Mitchell, Brendon; Shah, Vrajesh J.; Huang, Brady K.; Kent, William; Foran, Ian M.
Category: Ankle Introduction/Purpose: The sural nerve (SN) is a distal cutaneous nerve that provides sensation to the lateral foot and ankle, and is at risk of iatrogenic injury during surgery at the foot and ankle.1 Previous anatomic studies of the SN are limited to cadaveric studies with small sample sizes.2, 3, 4, 5, 6, 7, 8, 9 We analyzed a large cohort of high-field 3 Tesla (3T) magnetic resonance images (MRI) of the ankle to obtain a more generalizable, in-vivo sample of the distal course of the SN. A comparison of this in- vivo method of measurement vs. cadaveric studies may provide surgeons with a more accurate representation of SN anatomy and its relation to anatomic landmarks. Methods: We performed a retrospective review of 3T MRI studies of the ankle performed at our institution between January 2015 and December 2020. Three blinded reviewers measured the vertical distance of the SN to the distal tip of the lateral malleolus (DTLM), the horizontal distance of the SN to the DTLM, and the lateral border of the Achilles tendon (LBA) at the level of the DTLM. Also measured was the horizontal distance of the SN to the LBA at the level of superior Achilles insertion (SAI) onto the calcaneus as well, as 5 cm above the SAI. Intraclass correlation coefficient was calculated to assess reliability between reviewers. A total of 204 3T MRIs of the ankle were included. Results: The mean vertical distance from the SN to the DTLM was 2.2 +- 0.5 cm (ICC, 0.85; range 0.9-3.6 cm). The mean horizontal distance of the SN to the DTLM at the level of DTLM was 1.7 +- 0.3 cm (ICC, 0.98; range 0.8-3.0 cm). The mean horizontal distance of the SN to the LBA at the level of DTLM was 1.9 cm +- 0.3 cm (ICC, 0.91; range 1.0-2.9 cm). The mean horizontal distance from the SN to the LBA at the level of the SAI and 5 cm above the SAI was 2.6 +- 0.4 cm (ICC, 0.85; range 1.4-3.7 cm) and 0.9 +- 0.2 cm (ICC, 0.87; range 0.4-1.8 cm), respectively. Neither height nor BMI were strongly associated with the distance of the SN to any of our anatomic landmarks (R2 < 0.08 for all measurements). Conclusion: Several of our measurements summarized in differed from those reported in previous cadaveric studies. Although our mean horizontal distance of SN to LBA at SAI differed notably from cadaveric studies (2.6 cm vs 1.8-2.1 cm), a 2018 ultrasound study of the SN by Popieluszko et al observed a mean distance of 2.4 cm for this measurement. This concordance may indicate reliability between in-vivo methods of measurement vs. cadaveric studies. In-vivo measurements may also provide a more accurate representation of the anatomy, as these methods are not subject to the effects of embalming and dissection required of cadaveric studies.